Seawater quality conditions of the south Andaman Sea (Bay of Bengal, Indian Ocean) in lustrum during 2010s decade. (November 2018) - Franklin, Jayaseelan Benjamin; Sathish, Thadikamala; Vinithkumar, Nambali Valsalan; Kirubagaran, Ramalingam; Madeswaran, Perumal
Abstract: Andaman and Nicobar islands is one of the major tourism hubs of the World. Most travelers visit these islands for historical attractions, beaches, snorkeling, scuba diving, coral reefs, adventure and recreation. Port Blair is the capital and sole entry/exit point of these islands. The coasts of Port Blair Bay (PBB) and Wandoor Creek (WC) are largely populated due to its services offered to different public/private sectors and for the economic significance. Nevertheless, the global recognition of these islands relies on its healthy ecosystem. Effective management of beaches, bays and their environmental services requires knowledge of coastal water quality. This study assesses the datasets of twenty seawater quality parameters of PBB and WC generated during five years (2011–2015) at eight sites. Multivariate statistical techniques were used for (i) analysis and interpretation of water quality parameters (ii) identification of pollution factors/sources and (iii) understanding spatio-temporal variations valuable for coastal water quality management. Graphical abstract: Highlights: Half-decade seawater quality datasets were evaluated via multivariate statistical analysis. Assessment of long-term data aids to understand and establish spatial/temporal patterns. Results identified the key parameters and characteristics responsible for seawater quality. Investigation of intricate datasets facilitates future projected activities for ecosystem management.